2019
DOI: 10.6007/ijarbss/v9-i9/6274
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Transformational Leadership Style on Crisis Management in Yemen Organizations

Abstract: This study aims to examine the impact of transformational leadership style on crisis management and to examine the moderating effect of manager's crisis experience on the relationship between transformational leadership style and crisis management in Yemen organizations. Data was collected from 239 large private organizations in Yemen, through the self-administered questionnaire procedure. Partial Least Squares-Structural Equation Modelling (PLS-SEM) was employed in the data analysis. The result indicates that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…The result is consistent with research by Sobaih et al [ 17 ], Zumitzavan & Udchachone [ 24 ], and Cheung, King & Wong [ 26 ] that demonstrates the considerable impact of transformative leadership on hotel performance. Regarding the impact of transformational leadership on crisis management, the findings are consistent with those of a prior study [ [49] , [50] , [51] ] that demonstrated this impact to be positive and significant.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The result is consistent with research by Sobaih et al [ 17 ], Zumitzavan & Udchachone [ 24 ], and Cheung, King & Wong [ 26 ] that demonstrates the considerable impact of transformative leadership on hotel performance. Regarding the impact of transformational leadership on crisis management, the findings are consistent with those of a prior study [ [49] , [50] , [51] ] that demonstrated this impact to be positive and significant.…”
Section: Discussionsupporting
confidence: 89%
“…A significant criteria for this appointment should be the years of experience of the appointee. This is because this study, which supports the findings of earlier studies [ 49 , 70 , 72 ], shows that leaders with prior experience are more capable of ensuring sustained performance.…”
Section: Implications Of the Research Findings Limitations And Areas ...supporting
confidence: 91%
“…The purpose of this study, developed by Alkhawlani et al (2016), Mitroff et al (1987), andFink (1986), is to examine crisis management. More than 487 references refer to "Effective Crisis Management" by Mitroff et al (1987), as shown by the search engine.…”
Section: Methodsmentioning
confidence: 99%
“…Leader with a prior crisis experience , as indicated by Alkhawlani et al(2019)is more capable to handle the crisis situation.…”
Section: What Is the Degree Of Practicing Transformational Leadership...mentioning
confidence: 99%